Dual Crises Resilience: Financial Dynamics of ASEAN Tourism Firms - Widaryo, Chandika Mahendra; Kesuma, Muhammad Ramadhani; Henrika S, Margareth; Irianto, Ellen D. Oktanti; Nur, Aini Rohana; Ariswati, Lusiana Desy (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study examines the financial resilience of ASEAN tourism firms during the dual crises of the COVID-19 pandemic and Middle East geopolitical conflicts from 2019 to 2023, focusing on liquidity (Current Ratio) and solvency (Debt-to-Asset Ratio). Employing panel data regression on 160 observations from 32 publicly listed firms sourced from the Wall Street Journal, it analyzes the impact of revenue, earnings per share (EPS), and firm size. Findings indicate that revenue negatively affects liquidity, firm size enhances both liquidity and solvency, and EPS marginally reduces solvency. Larger firms demonstrate greater resilience, while smaller firms face vulnerabilities. The study highlights adaptive strategies like domestic tourism and digital transformation, offering insights for 2025 crises. Its novelty lies in its dual-crisis analysis within the ASEAN context, contributing to financial resilience literature and informing policies for liquidity management and non-debt financing.